1989
DOI: 10.1099/0022-1317-70-5-1253
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclosporin on Major Histocompatibility Complex-linked Resistance to Murine Cytomegalovirus

Abstract: SUMMARYThe ability of mice to survive infection with murine cytomegalovirus (MCMV) is known to be influenced by genes of the major histocompatibility complex (MHC). One hypothesis to account for this association is that MHC-linked resistance to MCMV is an 'immune response' gene effect, caused by differences in the strength of the MHCrestricted T cell response of mouse strains with different MHC haplotypes. Therefore, removal of T cell responses in mouse strains differing only at the MHC should render them equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…A comparative study of the susceptibility of athymic mice to MCMV suggested that host genotype influences the importance of T cell-mediated immunity . Furthermore, cyclosporin A treatment, which inhibits T cell function, has been shown to markedly increase the susceptibility to infection of BALB/c and A/J mice, but not that of more resistant mouse strains (Lawson et al, 1989). Thus, our first aim was to examine the importance of immunity mediated by T cell subsets in the control of MCMV infection in a panel of inbred strains of mice, including a second susceptible mouse strain (A/J), and two relatively resistant mouse strains (CBA/CaH and C5 7BL/10).…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of the susceptibility of athymic mice to MCMV suggested that host genotype influences the importance of T cell-mediated immunity . Furthermore, cyclosporin A treatment, which inhibits T cell function, has been shown to markedly increase the susceptibility to infection of BALB/c and A/J mice, but not that of more resistant mouse strains (Lawson et al, 1989). Thus, our first aim was to examine the importance of immunity mediated by T cell subsets in the control of MCMV infection in a panel of inbred strains of mice, including a second susceptible mouse strain (A/J), and two relatively resistant mouse strains (CBA/CaH and C5 7BL/10).…”
Section: Introductionmentioning
confidence: 99%
“…Athymic nude mice do not develop myocarditis following MCMV infection even though they disseminate the viral infection and produce higher titres of virus in many tissues [40]. Mice immunosuppressed with cyclosporin A showed a delayed onset of myocarditis by about 4 days and also produced higher titres of virus with an increased organ distribution of viral infection compared with untreated MCMV-infected mice [41]. In addition to antibodies reactive to MCMV antigens, autoantibodies to heart antigens, including reactivity to the heart contractile proteins, troponin, tropomyosin, myosin, and actin are found during acute MCMV infection of mice [6,42].…”
Section: Cytomegalovirusmentioning
confidence: 99%